Health care decision making autonomy of women from rural districts of Southern Ethiopia: a community based cross-sectional study - Alemayehu M; Meskele M (Dove Medical Press, 2017)
Mihiretu Alemayehu, Mengistu Meskele School of Public Health, College of Health Sciences and Medicine, Wolaita Sodo University, Wolaita Sodo, Ethiopia Introduction: Millions of women have little health care decision making autonomy in many cultures and tribes. African women are often perceived to have little participation in health care decisions. However, little has been investigated to identify factors contributing to decision making autonomy. Hence, it is important to obtain information on the contributing factors of decision making autonomy and disparities across different socio-cultural contexts. Methodology: A cross-sectional study was conducted in Wolaita and Dawro zones, Southern Ethiopia from February to March 2015. A total of 967 women were selected through multi-stage sampling. A survey was administered face-to-face through an interview format. EpiData v1.4.4.0 and SPSS version 20 were used to enter and analyze data, respectively. Proportions and means were used to describe the study population. Variables with P-value <0.2 in bivariate analysis were selected for multivariable regression. Finally, variables with P-value <0.05 in multivariable logistic regressions were identified as independent predictors. Odds ratios along with confidence intervals were used to determine the presence of association. Result: It was determined that 58.4% of women have autonomy, while 40.9% of study participants’ health care decisions were made by their husbands. The husband’s education (adjusted odds ratio [AOR] =1.91 [1.10, 3.32]), wealth index (AOR =0.62 [0.42, 0.92]), age (AOR =2.42 [1.35, 4.32] and AOR =7 [3.45, 14.22]), family size (AOR =0.53 [0.33, 0.85] and AOR =0.42 [0.23, 0.75]), and occupation (AOR =1.66 [1.14, 2.41]), were predictors of health care decision making autonomy. Conclusion: Even though every woman has the right to participate in her own health care decision making, more than two fifths of them have no role in making health care decisions about their own health. Husbands play a major role in making health care decisions about their wives. A comprehensive strategy needs to be implemented in order to empower women, as well as to challenge the traditional male dominance. Special attention has to be given to women living in rural areas in order to reduce their dependency through education and income generating activities. Keywords: decision making, women’s autonomy, health care decision, women’s empowerment, Wolaita, Dawro, Southern Ethiopia